(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Mridbhakshanjanya Pandu, an Ayurvedic condition correlated with iron deficiency anemia due to pica, is a prevalent disorder in pediatric populations, particularly in low socioeconomic settings. This case study presents a 7-year-old male with symptoms including pallor, fatigue, and habitual consumption of non-nutritive substances like clay and wall putty. Clinical and laboratory investigations confirmed iron deficiency anemia. The child was treated with a combination of Kesharadi Ghrita, a classical Ayurvedic formulation known for its Pitta-pacifying and digestive-enhancing properties, along with conventional ferrous ascorbate therapy over a 45-day period. Outcomes were assessed through symptomatic improvement and hematological parameters including hemoglobin levels, MCV, and RDW-CV. Notable clinical improvements were observed- pallor reduced from moderate to mild, appetite normalized, and pica behavior ceased. Hemoglobin levels rose from 8.2gm/dL to 10.3gm/dL without any reported side effects. The therapeutic role of Kesharadi Ghrita may be attributed to its Agni Deepana (digestive stimulant), Krimighna (anthelmintic), and Rasa Dhatu Poshana (nutritive) properties, which possibly enhanced iron absorption and corrected the underlying pathology. This case supports the integrative use of Ayurvedic interventions in pediatric anemia and highlights the need for further studies to evaluate the broader applicability of Kesharadi Ghrita in similar clinical contexts.